Synthesized BiVO4 was by the co-precipitation method for Rhodamine B degradation under visible light - Nguyen, Trinh Duy; Cao, Vu Dai; Nguyen, Vinh Huu; Xuan Nong, Linh; Duy Luu, Tuan; Vo, Dai-Viet N.; Do, Sy Trung; Lam, Tri Duc (IOP Publishing, 2019)
Recently, BiVO4 photocatalysts has been received much attention in field of catalysts. Because it can be used to degrade harmful organic catalysts in visible light, irradiation produces CO2, H2O and less harmful organic matter. In this study, we have successfully synthesized a BiVO4 photocatalysts via co-precipitation method in the presence of urea and different calcined temperatures. The survey calcined temperatures as 300°C; 350°C; 400°C and 450°C. The obtained materials were characterized by Scanning electron microscope (SEM) and X-ray diffraction (XRD). The photocatalytic activity was evaluated by the photocatalytic degradation of rhodamine B (RhB) degradation under visible compact Philip lamp (40W) light irradiation. The result indicates that all samples calcined are monoclinic scheelite structure of BiVO4. The BiVO4-350°C sample performed the best in the photodegradation of RhB.